EXPORT COMPETITIVENESS ANALYSIS OF COFFEEINDONESIAIN THE WORLD MARKET - desi ratna sari; ermi tety (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: The purpose of this study was to analyze the competitiveness of Indonesian coffee in the world market. The data used in this study was a secondary data export raw coffee Indonesia, Brazil, Vietnam and Colombia during the period 2001-2012. The data was taken from the value and volume of exports of coffee in the world market. The analytical method used was the Revealed Comparative Advantage (RCA) and Constant Market Share Analysis (CMSA). This data indicated that Indonesia has a RCA exports of coffee were getting better every year because has the positive values. Meanwhile the CMSA analysis note that the competitiveness of Indonesia's coffee exports more influenced by market distribution and competitiveness effects. This represents an increase of Indonesia's coffee exports more influenced by the growth of the world's coffee export in the marketing of coffee to importing countries that have a high demand.Keywords:coffee, competitiveness, Revealed Comparative Advantage (RCA), Constant Market Share analysis (CMSA)